2013
DOI: 10.1042/cs20130538
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-122 down-regulation may play a role in severe myocardial fibrosis in human aortic stenosis through TGF-β1 up-regulation

Abstract: miRNAs (microRNAs) have been shown to play a role in myocardial fibrosis. The present study was designed to analyse whether alterations in miRNA expression contribute to the progression of myocardial fibrosis in AS (aortic valve stenosis) patients through up-regulation of the pro-fibrotic factor TGF-β1 (transforming growth factor-β type 1). Endomyocardial biopsies were obtained from 28 patients with severe AS, and from the necropsies of 10 control subjects. AS patients presented increased myocardial CVF (colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 39 publications
1
59
0
2
Order By: Relevance
“…Kessler et al, 1990) and its expression increases in fibrosis in parallel to the characteristic increase in collagen expression (Ogata et al, 1997;Shalitin et al, 2003;Kessler-Icekson et al, 2006;Yu et al, 2013;Beaumont et al, 2014). Thus, PCPE-1 seems to function as a specific positive regulator of collagen deposition.…”
Section: Introductionmentioning
confidence: 84%
“…Kessler et al, 1990) and its expression increases in fibrosis in parallel to the characteristic increase in collagen expression (Ogata et al, 1997;Shalitin et al, 2003;Kessler-Icekson et al, 2006;Yu et al, 2013;Beaumont et al, 2014). Thus, PCPE-1 seems to function as a specific positive regulator of collagen deposition.…”
Section: Introductionmentioning
confidence: 84%
“…Also, since PCPE-2 is relatively highly expressed in heart, cardiac fibrosis induced in Pcolce2 −/− mice by transverse aortic constriction was studied and found to result in lower collagen deposition, compared to wild-type, with reduced myocardial stiffness and increased survival [96]. Finally, the first study of PCPE-1 expression conducted on human samples showed a significant increase of protein levels in myocardial fibrosis linked to aortic valve stenosis [97]. These latter results support the potential of PCPEs as new targets for anti-fibrotic therapies.…”
Section: New Targets For Therapy Fibrosismentioning
confidence: 97%
“…Left ventricular (LV) pressure overload, as seen in patients with aortic stenosis, increases transforming growth factor beta (TGF-β) signaling [1]. This, in turn, activates cardiac fibroblasts (CFB) and leads to myocardial fibrosis due to increased CFB production of extracellular matrix (ECM) i.e.…”
Section: Introductionmentioning
confidence: 99%